Six-month Change In Cancer Survivors Ratings Of Distress With Pandemic Closure Of Exercise Rehabilitation Clinics...2021 ACSM Annual Meeting & World Congresses [Virtual], June 1-5, 2021 - Holmes, Kristina Kay; LoRusso, Stephen M.; Wisniewski, Kristofer; Heitzenrater, Jared; Baker, Stephen; Wonders, Karen; Teranashi-Hashimoto, Cheri; Yamada, Paulette (Medicine & Science in Sports & Exercise)
PURPOSE: Distress, the sixth vital sign of cancer care is experienced throughout survivorship1. Albana2 reports COVID-19 has increased mental health issues in survivors. The impact of Pandemic restrictions on survivors actively involved in structured exercise programing has not been explored. The distress thermometer, a 39 item, 5 category tool rates distress on a 10-point scale, and identifies problem area sources of distress.1Purpose To identify 6 month changes in levels and sources of Distress in survivors due to closure of Cancer Exercise Rehabilitation Clinics. METHODS: 150 Cancer Survivors responded to a modified NCCN Distress Thermometer administered via Survey Monkey in March 2019 and Sept 2020. We added 14 items in Exercise and COVID categories. Time 1 and 2 ratings of distress, identification of problems and Pearson correlations with exercise items were determined. A rating >4 indicates high distress1. 10% min percent cut point was category source of distress. This study was approved by the SFU IRB. RESULTS: Mean patient time 1 distress = 4.14 (N=47) and time 2 = 4.20 (N=103). Mean sources of distress time 1 and 2: Practical Problems (12% to 19%), Family Problems (21% to 26%), Emotional Problems (44% to 48%), Spiritual/ Religious (17% to 19%), Physical Problems (12.5% to 22%), COVID-19 Concerns (23% to 15%), Exercise Concerns (39% to 41%). Significant (p<.05) low to moderate correlations (r<0.29) of Depression: Loss of Fitness, Loss of Strength; Anxiety: Exercise Clinic Closing; Sadness: Loss of Fitness, Loss of Strength; Worry: Loss of Fitness; Fear of Recurrence: Loss of Fitness, Loss of Strength, Fatigue, Current Exercise Support/Guidance CONCLUSIONS: Patients maintained clinical distress during 6 month Pandemic restrictions. Minimum thresholds of concern were met in all categories and increased in time 2. Decreased time 2 COVID Concerns suggests some accommodation to restrictions. As reported distress > 4 links strongly with emotional concerns1. Exercise concern appears too as well. This data suggests that structured exercise programming contribution to emotional wellbeing in this patient population should not be underestimated. It also supports Albano2 reporting mental health issues in survivors during the Pandemic. 1. Ownby KK et al (2019) J Adv Pract Oncol 10(2)175-179 2. Albana D et al (2020) JNP